A from‐benchtop‐to‐desktop workflow for validating HTS data and for taxonomic identification in diet metabarcoding studies. (20th September 2017) - Corse, Emmanuel; Meglécz, Emese; Archambaud, Gaït; Ardisson, Morgane; Martin, Jean‐François; Tougard, Christelle; Chappaz, Rémi; Dubut, Vincent
Abstract: The main objective of this work was to develop and validate a robust and reliable "from‐benchtop‐to‐desktop" metabarcoding workflow to investigate the diet of invertebrate‐eaters. We applied our workflow to faecal DNA samples of an invertebrate‐eating fish species. A fragment of the cytochrome c oxidase I (COI) gene was amplified by combining two minibarcoding primer sets to maximize the taxonomic coverage. Amplicons were sequenced by an Illumina MiSeq platform. We developed a filtering approach based on a series of nonarbitrary thresholds established from control samples and from molecular replicates to address the elimination of cross‐contamination, PCR/sequencing errors and mistagging artefacts. This resulted in a conservative and informative metabarcoding data set. We developed a taxonomic assignment procedure that combines different approaches and that allowed the identification of 75% of invertebrate COI variants to the species level. Moreover, based on the diversity of the variants, we introduced a semiquantitative statistic in our diet study, the minimum number of individuals, which is based on the number of distinct variants in each sample. The metabarcoding approach described in this article may guide future diet studies that aim to produce robust data sets associated with a fine and accurate identification of prey items.